CFD modelling of CO₂ removal from natural gas using graphene based membrane: article - Hamdi, Rabiatul Adawiyah; Md. Yusop, Nadiahnor; Othman, Nurhidayati (2019)
The modeling of CO₂ removal from CO₂/CH₄ mixture is performed using the Ansys Fluent 15.0 software. The effect of thickness of polyethersulfone-reduced graphene oxide-zeolitic imadozole framework 8 (PES/RGO-ZIF8) membrane and the feed pressure on the ability of membrane to remove CO₂ are investigated. The increment of thickness resulted in the increase of CO₂ removal. Meanwhile, the increase of feed pressure causes the CO₂ permeance to reduce. Various parameters should be manipulated in order to obtain more accurate and reliable result of membrane’s performance in gas separation process